STUDYING FAR FROM HOME: A CLOSER LOOK AT INTERNATIONAL STUDENTS’ STRUGGLES - Tolipjonova Sevara Rustam qizi (World Scientific Research Journal, 2025)
After graduating from high school, many students dream of studying abroad to pursue their tertiary education. But does it always come down with only advantages? The answer is not always positive. This article explores key challenges faced by international students studying away from home. Emotional, financial and academic struggles are explored with the help of a literature review and qualitative research. Through interviews with international students, key barriers are identified and recommendations for universities are proposed. The article highlights the importance of support to improve the international student experience.